Combination of Methyl from Methane Early Cracking: A Possible Mechanism for Carbon Isotopic Reversal of Overmature Natural Gas. (10th January 2022) - Mi, Jingkui; He, Kun; Shuai, Yanhuan; Guo, Jinhao
Abstract : In this study, a methane (CH4 ) cracking experiment in the temperature range of 425–800°C is presented. The experimental result shows that there are some alkane and alkene generation during CH4 cracking, in addition to hydrogen (H2 ). Moreover, the hydrocarbon gas displays carbon isotopic reversal (δ 13 C 1 > δ 13 C 2 ) below 700°C, while solid carbon appears on the inner wall of the gold tube above 700°C. The variation in experimental products (including gas and solid carbon) with increasing temperature suggests that CH4 does not crack into carbon and H2 directly during its cracking, but first cracks into methyl (CH3 ⋅ ) and proton (H + ) groups. CH3 ⋅ shares depleted 13 C for preferential bond cleavage in 12 C–H rather than 13 C–H. CH3 ⋅ combination leads to depletion of 13 C in heavy gas and further causes the carbon isotopic reversal (δ 13 C 1 > δ 13 C 2 ) of hydrocarbon gas. Geological analysis of the experimental data indicates that the amount of heavy gas formed by the combination of CH3 ⋅ from CH4 early cracking and with depleted 13 C is so little that can be masked by the bulk heavy gas from organic matter (OM) and with enriched 13 C at R o < 2.5 % . Thus, natural gas shows normal isotope distribution (δ 13 C 1 < δ 13 C 2 ) in this maturity stage. CH3 ⋅ combination (or CH4 polymerization) intensifies on exhaustion gas generation from OM in the maturity range of R o > 2.5 % . Therefore, the carbon isotopic reversal of natural gas appears at the overmature stage. CH4 polymerization is a possible mechanism for carbon isotopic reversal of overmature natural gas. The experimental results indicate that although CH4 might have start cracking at R o > 2.5 %, but it cracks substantially above 6.0% R o in actual geological settings.